Comparison of intramedullary nailing and minimal invasive plate osteosynthesis in the treatment of simple intra-articular fractures of the distal tibia (AO-OTA type 43 C1-C2) - Ozan Beytemür; Alican Barış; Cem Albay; Serdar Yüksel; Sever Çağlar; Ender Alagöz (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to compare midterm functional and radiographic results of minimal invasive plate osteosynthesis (MIPO) with intramedullary nailing (IMN) of simple intra-articular distal tibial fractures (AO-OTA type 43 C1-C2). Methods: Seventy-three simple intra-articular distal tibial fracture patients were evaluated retrospectively. All were treated between 2009 and 2014. The average age of the patients was 40.3 years. Thirty-seven patients were treated with IMN and 36 patients were treated with MIPO. Fibular plate osteosynthesis was applied in 5 cases (13.5%) in the IMN group and in 23 patients (63.9%) in the MIPO group. Results: Functional results and complications of IMN and MIPO methods were assessed in 73 patients. The average union time was 16.4 ± 2.7 weeks in the IMN group and 15.2 ± 1.8 weeks in the MIPO group (p = 0.079). The average Olerud-Molander Ankle Score was 87.8 ± 8.1 in the IMN group and 81.5 ± 11.8 in the MIPO group (p = 0.013). Four patients in the IMN group experienced valgus malunion, while it was not observed in any patients in the MIPO group (p = 0.042). Recurvatum malunion was detected in 10 patients in the MIPO group and not seen in the IMN group (p = 0.001). Ankle dorsiflexion angle was 25.8 ± 4.5° in the IMN group and 33.3 ± 8.9° in the MIPO group (p = 0.000). Conclusion: Simple intra-articular distal tibial fractures are successfully treated with IMN and MIPO. Prevalence of valgus malunion was higher in the IMN group and recurvatum was more prevalent in the MIPO group. MIPO is the first preference according to the literature; however, successful results have been obtained with IMN in this fracture pattern. Level of Evidence: Level III, Therapeutic Study. Keywords: Distal tibial fractures, Intra-articular fractures, Intramedullary nailing, Minimally invasive plate osteosynthesis, Minimally invasive surgery